Reflecting on the 11th International Equine Infectious Diseases Conference. (9th September 2022) - Kydd, Julia; Nielsen, Martin; Waller, Andrew
Abstract : Julia Kydd, Martin Nielsen and Andrew Waller highlight some of the key presentations given at last year's 11th International Equine Infectious Diseases Conference, which was held virtually.